Pengaruh Minat Belajar Dan Teman Sebaya Terhadap Prstasi Belajar Siswa Kelas VIII di SMP Negeri 12 Pematang Siantar - Damayanti Mariani Haloho; Anton Luvi Siahaan; Anggun Tiur Ida Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to obtain knowledge about the influence of learning interests and peers on the learning achievement of grade VIII students at SMP Negeri 12 Pematang Siantar for the 2023/2024 academic year. This type of research is quantitative with an ex-post facto approach with the testing media used is SPSS 22. The total population in this study was 286 people, and the sample used was 170 people. The sample collection technique used is the Proportionate Stratified Random Sampling Technique. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and coefficient of determination (R2). The results stated that: 1) There was a positive and significant influence of learning interest on learning achievement, this result was seen in the t test where the t value calculated from learning interest (5,710) > the t value of thetable (1.6, 540) which means that the variable is significant. (2) There is a positive and significant influence of peers on student learning achievement, this result is seen in the t test where and thecalculated t value of peers (3.020) > ttable (1.6540) which means that the variable is significant. 3) Learning interests and peers (together affect student achievement this result can be seen in the F test wherethe calculated F value (34.117) >the table F value (3.0501). The R Square coefficient of determination test is known to be 0.291, which means 29.1% of learning interest and peer variables on the learning achievement of grade VIII students of SMP Negeri 12 Pematang Siantar. While 70.9% is the influence of other variables that were not studied in this study.,